Penguatan Moderasi Beragama melalui Pembelajaran Pendidikan Islam pada Mahasiswa STAI Al-Amin Gersik Kediri Lombok Barat NTB - Andrian Firdaus (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study aims to analyze the role of Islamic education in strengthening religious moderation among university students. The research background is based on the increasing need to build tolerance, control extremism, and foster interfaith dialogue in a pluralistic campus environment. In the context of higher education, Islamic education plays a strategic role as a means of character development for students, enabling them not only to understand religious teachings normatively but also to implement moderate Islamic values in their social lives. The research method used a qualitative approach with a case study technique in several study programs at STAI Al-Amin Gersik Kediri, West Lombok, NTB. Data collection techniques were conducted through observation, interviews, and documentation of the implementation of Islamic Education learning for students. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions to obtain a comprehensive picture of the implementation of religious moderation in the learning process. The results of the study show that Strengthening Religious Moderation through Islamic Education Learning has a positive impact on increasing students' understanding of the importance of tolerance, anti-radicalism, respect for diversity, and critical thinking skills in understanding religious issues.